First record of the genus Megalota Diakonoff from China, with the descriptions of two new species (Lepidoptera: Tortricidae: Olethreutinae) - Yu, Haili; Li, Baoguo (Zootaxa, 2013)
Megalota Diakonoff, 1966 is reported from China for the first time. Two new species, M. bicepsunca, sp. nov., and M. curvativa, sp. nov., are described and illustrated based on the male adults, both of them are distributed in south China. Photographs of the adults and male genitalia are provided.